New Media and Arab-Israeli Conflict: Dynamics, Impact And Challenges - Lokman, Ainul Asyraf; Mohd Nor, Mohd Roslan; Abdul Hamid, Faisal @ Ahmad Faisal (Journal Al-Muqaddimah, 2023)
With the advent of new media 5.0, national and ethnic identities in the Arab-Israeli conflict have been altered, and social media has become a crucial source of communication and information for both factions involved in the conflict. These platforms have raised questions about the influence of social media on the formation of national and ethnic identities during conflict. The objective of this paper is to examine the role of new media especially social media in shaping national and ethnic identities in the Arab-Israeli conflict. This paper will conduct a comprehensive review of existing literature and studies on the topic. The findings of this study revealed that new media has had a significant impact on shaping national and ethnic identities in the Arab-Israeli conflict. Social media platforms have provided a space for people on both sides of the conflict to express their opinions and connect with others who share their views. However, social media has also facilitated the spread of misinformation, propaganda, and hate speech, which has reinforced existing biases and deepened divisions between groups. The paper also highlights the potential of new media in supporting conflict resolution efforts, such as by facilitating dialogue and promoting understanding. The study suggest governments, media practitioners, and civil society players to handle new media concerns in the Arab-Israeli conflict. This involves fighting misinformation and hate speech, encouraging social media responsibility, and using new media to resolve conflicts.